floprovides
floprovides
01-09-2017
Mathematics
contestada
g(x)= 3x − 3; Find g(−6)
Respuesta :
wikk
wikk
01-09-2017
g(x)= 3x − 3
g(−6)
g(-6) = 3(-6) - 3
g(-6) = -18 - 3
g(-6) = -21
The answer is -21.
Answer Link
choixongdong
choixongdong
01-09-2017
g(−6) =
3(-6) − 3 = -18 - 3 = -21
answer
g(−6) = -21
Answer Link
VER TODAS LAS RESPUESTAS ( 79+ )
ACCESS MORE
Otras preguntas
Why is September 16 so important for Mexico
Describe where is the fertile crescent located where mesopotania located
Thomas' grandfather is 100. Thomas' grandfather is 10 times older then Thomas.How old is Thomas?
a natural solid that has its particles arranged in a crystal pattern is called
7849 rounded with the 7 underlined
what is 4/20 simplified
Which describes a major challenge facing the builders of the transcontinental railroad?
What happens to water molecules during the boiling process?
A family uses 12,986.64 Swiss francs per year to pay a mortgage that requires US dollars. Approximately how much, in US dollars, does the family spend per month
1. What was the Munich conference? Why did the French and British give into Hitler's demands?